Hubungan Antara Status Gizi Dengan Tingkat Kebugaran Jasmani Siswa SMA Negeri 1 Kahayan Hilir Kabupaten Pulang Pisau - Cukei Cukei; Bernisa Bernisa; Siskaevia Siskaevia (FKIP Universitas Palangka Raya, 2024)
Physical fitness is a person's ability to carry out daily activities optimally without experiencing significant fatigue and still having energy reserves to carry out the next activity. In physical fitness there are several influencing factors, namely internal and external factors. Internal factors include genetics, age, gender, while external factors are nutritional status, physical activity, exercise habits and others. This research aims to determine the relationship between nutritional status and the level of physical fitness of students at SMA Negeri 1 Kahayan Hilir, Pulang Regency. Knife. This research is correlational research with a non-experimental research design. The population in this study were students of SMA Negeri 1 Kahayan Hilir, Pulang Pisau Regency with a population of 280 students and the sample for this study was class X, class sampling. The instrument in this study uses nutritional status measurements based on Body Mass Index according to Age (BMI/U), while to measure physical fitness levels using the MFT (Multistage fitness test) test instrument. For data analysis used is the gamma correlation coefficient. From the results of statistical calculations it shows a value of 0.227 and a sig of 0.564, this shows that sig (0.564) > alpha 0.05 which means that H0 is accepted and H1 is rejected. Thus, it can be concluded that there is no significant relationship between nutritional status and the level of physical fitness of students at SMA Negeri 1 Kahayan Hilir, Pulang Pisau Regency, because there are several other factors that influence the level of physical fitness, for example physical activity and exercise habits.